The prevention of pericarp browning and the maintenance of post-harvest quality in vietnamese longan cv. long, using sodium metabisulfite treatment - Le Ha Hai (2018)
The impact of sodium metabisulfite (Na 2S 2O 5) treatment on the prevention of pericarp browning and the maintenance of the postharvest quality of Vietnamese longan cv. Long during storage was studied by soaking bunches of the fruit in 2.5 or 5 or 7.5% of sodium metabisulfite solution for 5 and 10 min at room temperature and then storing them at 5±1°C for 28 days. The visual appearance expressed as pericarp and flesh color; the lightness of fruit pericarp (L* value); the yellowness of fruit pericarp (b* value); polyphenol oxidase (PPO) activity; the percentage of fruit decay and fruit drop; total soluble solids (TSS) content were studied. The results show that the 10 min soaking treatment in 7.5% sodium metabisulfite solution maintained L* and b* values and low PPO activity, with the fruit showing no signs of severe pericarp browning or fruit decay throughout the 21 days in storage. Moreover, the postharvest quality of the longan fruit revealed no difference over time; plus the percentage of fruit drop was only 5.2%, when compared with the control was 5.8% and other treatments ranged from 5.5 to 5.9%. © 2011 Friends Science Publishers.